PERENCANAAN PROGRAM PENGEMBANGAN BUDI DAYA PERIKANAN DI DINAS KELAUTAN DAN PERIKANAN KABUPATEN MAMUJU UTARA - Jumiati, Burhan (Katalogis, 2016)
This study aims to identify and analyze the planning of development programs in aquaculture ponds in the Department of Fisheries Keluatan and North Mamuju regency. This type of research uses descriptive qualitative approach, measuring the program planning based on the opinions Glen in Adi (2004: 81) include: responsive planning aspects, aspects of community involvement and collaboration aspects. The collection of data through observation, interview, and documentation, analyzed through the stages of data reduction, data display, and conclusion. The study concluded that, not paying attention responsive planning as activity planning program activities developing aquaculture (sea and land) that are based on the formulation of the problems faced by farmers/ fishermen, not pay attention to the planning community involvement in the preparation of action plan development programs in aquaculture (sea and land) by actively involving the farmers/ fishermen. Preparation of program development of aquaculture is not maximized increase incomes for the welfare and independence, because it does not involve the target communities, and not pay attention to the planning of collaboration in the preparation of action plan development program aquaculture (sea and land) on the basis of cooperation between intansi-related technical stakeholders (community organizations, community groups and farmers / fishermen). A form of collaboration which is inter-related SKPD, face many obstacles due to the head SKPD still think that the problem domain of fisheries development is the responsibility of the Department of Marine and Fisheries, and no association with other officials.